Penguatan Kapasitas Pengelolaan Radio Komunitas Merapi-Merbabu Community (Mmc-Fm) Melalui Pelatihan Penyusunan Program Siaran Berbasis Mitigasi Bencana Dan Pangan Lokal Di Kawasan Lereng Merapi Desa Samiran Selo Boyolali - Setiawan, Topan; Putro, Fanny Hendro Aryo; Hertini, Etty Sri; Muryanto, Sigit; Chumaeson, Wahyuning; Wicaksana, Aliffia Harsa; Santoso, Bagas (Journal Of Human And Education (JAHE), 2024)
The main and urgent focus of the service that will be carried out is an effort to increase the capacity of target partners with training, initiation and AMT (Achievement Motivation Training). The PKM subjects or target partners are given these three treatments, so that the objectives of the PKM activities or programs that have been previously determined will be achieved as well as possible. The focus of the next service is carried out due to the reality in the field of how weak the management aspect is, which is indicated by several facts, namely (1) broadcasts are carried out sporadically adjusting to the "inner mood" of the managers, so that what is felt by the audience of farmers who listen is that sometimes there are broadcasts and sometimes there are none at all, (2) broadcasts tend to be monotonous in this context there are no programs related to the green economy based on varied local potential, (3) The radio crew seems to be the same, only 5 people are actively broadcasting, so that the existing conditions from the perspective of broadcast management show the condition of the zero regeneration of the crew / managers of the community radio. The method in this activity is a workshop on making broadcast programs based on local agriculture. This activity pays attention to the community's experience of agriculture as a basis for the team in determining the training concept. The approach used is adult education or andragogy, which includes discussions, problem solving, simulation exercises, and direct practice. With this program, community radio can become an important pillar in community empowerment, not only in dealing with disasters but also in maintaining the sustainability of local food. With these steps, community radio can become a sustainable, independent, and useful medium for local communities. This sustainability is not only seen from the financial aspect, but also in terms of active community involvement and the relevance of its programs to community needs.